HIGH INTENSITY INTERVAL TRAINING LEBIH MENINGKATKAN KAPASITAS AEROBIK DARIPADA LOW INTENSITY STEADY STATE PADA ATLET KARATE DOJO CAMPUHAN ASRI DI DENPASAR - I Ketut Wedarthana Aditya Prana; I Putu Gede Adiatmika; Tjokorda Gde Bagus Mahadewa; Dewa Putu Sutjana; Ketut Tirtayasa; I Putu Adiartha Griadhi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2019)
Decreased physical endurance impacts for human fitness. The occurrence of decline in activities that can make physical decline of heart and lung function and decreased metabolic system. This physical endurance is divided into two parts, namely general durability and muscular endurance. This research aims to know HIIT training further increase aerobic capacity than in training of LISS in Dojo Campuhan Asri Denpasar. Type of experimental research with the randomized pre-posttest control group design. Aerobic capacity is measuring by MFT (multistage fitnest test). The research subjects were male karate athletes between 7-12 years, totaling 16 people and divided into two different treatment groups. Group I was given training in High Intensity Interval Training with training based on maximum repetition and Group II was given Low Intensity Steady State training with training based on a maximum time of 60 minutes with frequency of exercise 3 times a week for 6 weeks in both group. The result of increased aerobic capacity between the two Groups before and after the training was tested with t-independent, with the significant value ? = 0.05. Average aerobic capacity in both Groups before training with the value P = 0.339 and after training with the value P = 0.001. It shows that the group I and group II both gave an improved effect (P < 0.05). But in group I better than the group II (p < 0.05). It was concluded that aerobic capacity in Group I and Group II had both increased. However, the High Intensity Interval Training Group training is better than the Low Intensity Steady State Training Group. High Intensity Interval Training suggested training is recommended for athletes training. Keywords: High Intensity Interval Training , HIIT , Low Intensity Steady State, LISS, Capacity Aerobic, Karate.